How reliable is the diagnosis of lung cancer using small biopsy specimens? Report of a UKCCCR Lung Cancer Working Party. Issue 11 (November 1993) - Thomas, J S; Lamb, D; Ashcroft, T; Corrin, B; Edwards, C W; Gibbs, A R; Kenyon, W E; Stephens, R J; Whimster, W F
Abstract : BACKGROUND--A study was undertaken to investigate the accuracy of typing of a series of bronchial carcinomas by experienced pathologists with an interest in lung cancer from the examination of bronchoscopic biopsy specimens. METHODS--Eighty bronchial biopsy specimens showing positive results for bronchial carcinoma were circulated to five pathologists, who recorded diagnostic criteria and diagnosis for each. Diagnoses were then compared with the diagnosis agreed from the resection specimen corresponding to each biopsy specimen. A "non-small cell carcinoma, not further specified" classification group was introduced for small biopsy specimens. RESULTS--A diagnostic accuracy of 75% was achieved for squamous cell carcinomas, 66% for small cell carcinomas, and 50% for adenocarcinomas. There was diagnostic confusion between small cell and non-small cell carcinoma in less than 10% of cases. The introduction of a non-specific non-small cell classification improved diagnostic accuracy by 10-15% for each non-small cell tumour group. CONCLUSIONS--There are appreciable inaccuracies in applying the World Health Organisation's 1981 classification of lung cancer to the diagnosis of bronchial carcinoma from small biopsy specimens and these inaccuracies have been measured. They can be diminished by introducing a less specific "non-small cell" category for use with this sort of biopsy material. Care should be taken not to overinterpret small biopsy specimens in lung cancer.